2014
DOI: 10.12968/bjon.2014.23.1.32
|View full text |Cite
|
Sign up to set email alerts
|

The role and development of consultancy in nursing practice

Abstract: The term consultancy is used in many contexts. It has been applied to advanced nursing practice roles such as clinical nurse specialist, advanced nurse practitioner, nurse practitioner and other occupations. This causes confusion in the healthcare setting as the word is often used interchangeably between roles and has traditionally been used in a medical context. In addition, the development of nurse consultant posts has further compounded the uncertainty around consultancy. However, regardless of the role hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…For example, in Mitchel and Doody's study, some physicians provided appropriate support for the nurse consultants, or even clinical autonomy and independent performance have been reported in the work of nurse consultants, and their positions have been reported to similar to those of physicians (physician as equal partners). [2526] In some studies, nurses have been seen less as an obstacle, and nurse consultants have been satisfied with their job, suggesting that job motivation and satisfaction of nurses in advanced countries is higher than in Iran. The high levels of satisfaction of nurse consultants with their role in other countries has been reported to be due to the independence of the patients and the importance of role for them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Mitchel and Doody's study, some physicians provided appropriate support for the nurse consultants, or even clinical autonomy and independent performance have been reported in the work of nurse consultants, and their positions have been reported to similar to those of physicians (physician as equal partners). [2526] In some studies, nurses have been seen less as an obstacle, and nurse consultants have been satisfied with their job, suggesting that job motivation and satisfaction of nurses in advanced countries is higher than in Iran. The high levels of satisfaction of nurse consultants with their role in other countries has been reported to be due to the independence of the patients and the importance of role for them.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in many articles, nurses received adequate support from the organization, physicians, and nurse colleagues. [414243] Franks also reported that the development of this role occurs not only through clinical needs but also through political motives such as the need for the development of nursing roles and economic change. [17] Therefore, these results are consistent with our results that demonstrate the necessity of support of nurse consultants and introducing it to organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in America and Canada, advanced roles of the nursing profession have been identified in the international literature for more than 40 years. However, specialisation in nursing cannot yet be adopted in Europe (Donald et al., 2010; Doody, 2014; Pulcini et al., 2010). Although some universities in Europe use specialisation programmes, there is still a lack of information about the role of SN in terms of its definition, aim and educational requirements.…”
Section: Introductionmentioning
confidence: 99%